2023
DOI: 10.1080/15592324.2023.2216001
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of gamma-aminobutyric acid and melatonin on seed germination and cadmium tolerance in tomato

Abstract: The effects of exogenous γ-aminobutyric acid (GABA) and melatonin (MT) on tomato seed germination and shoot growth exposed to cadmium stress were investigated. On the one hand, treatment with MT (10–200 μM) or GABA (10–200 μM) alone could significantly relieve cadmium stress in tomato seedlings, which is reflected in increasing the germination rate, vigor index, fresh weight, dry weight and radicle lengths of tomato seeds, as well as the soluble content compared to the absence of exogenous treatment, and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…35 Studies have shown that different melatonin concentrations have different effects on tomato biomass under stress conditions. 36 Our study on grapes was similar to its results in that in the pre-stress period, the dry fresh weight of grape roots and leaves was significantly increased under M50, M100, and M150 treatments. And all of them reached the maximum accumulation in the M50 treatment.…”
Section: Discussionsupporting
confidence: 87%
“…35 Studies have shown that different melatonin concentrations have different effects on tomato biomass under stress conditions. 36 Our study on grapes was similar to its results in that in the pre-stress period, the dry fresh weight of grape roots and leaves was significantly increased under M50, M100, and M150 treatments. And all of them reached the maximum accumulation in the M50 treatment.…”
Section: Discussionsupporting
confidence: 87%
“…The germination of crops like Solanum lycopersicum [50], Triticum aestivum [51], and Oryza sativa [52] is severely hindered by Cd contamination in soil. However, there is little research about the impact of Cd stress on the germination of C. auriculatum.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Cadmium, one of the potential harmful metals that enters into the soils from industrial and agricultural sources, is considered hazardous, harmful, and toxic. 3 , 4 It is water soluble and mobile in nature. 4 Plants do not require Cd and excessive amounts of Cd in plants may impair their metabolic activities.…”
Section: Introductionmentioning
confidence: 99%